TEACHERS' UNDERSTANDING OF TEXT TYPES INTEACHING READING OF EFL CLASSROOMS - Endi, - (2014)
This study was focused on teachers' understanding of text types in teaching reading of EFL classrooms. The study used a case study design. The data were collected through interviews and classroom observations. The data were analyzed based on research questions. The analysis of data revealed that the teachers understood text types theoretically but they did not perform teaching reading procedurally and communicatively; for example, steps of teaching reading was not consistent, classroom interaction was not communicative. Through this study, the writer recommends that the teachers should plan teaching reading procedures, select interesting materials, use supporting media, master classroom languages, communicate among students communicatively, give appropriate reading tests, and use manageable time.